The impact of immune checkpoint inhibition on atherosclerosis in cancer patients - Han, Rui; Wang, Sheng Han; Tian, Jingchao; Zhou, Shanshan (Frontiers in Immunology, 2025)
The emergence of immune checkpoint inhibitors (ICIs) have provided a new perspective for cancer immunotherapy. Immune checkpoint inhibitors significantly improve the survival prognosis of patients with various advanced cancers by inhibiting immune checkpoint molecules, thereby releasing the suppression of T cells by tumor microenvironment, such as cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1). Immune checkpoint inhibitor (ICI) therapy, while effective, gives rise to distinct immune-related adverse events (irAEs), including cardiovascular toxicities, necessitating focused research efforts to better understand and address these specific complications. The myocarditis-associated toxicity has been extensively studied. This article reviews the latest clinical and preclinical literature on the epidemiology and pathogenesis of ICI-related atherosclerosis, explores the pathophysiological mechanisms by which ICIs promote atherosclerosis, and discusses risk assessment, identification and monitoring methods, and intervention strategies for ICI treatment related atherosclerosis.